The Crises of Medieval Society: The Mongol Invasion in Eastern and Central Europe - Font, M. (Україна: культурна спадщина, національна свідомість, державність, 2011)
The Mongol invasion between 1240 and 1242 is one of the best known events of
the Middle Ages, in fact, to an extent that it has lost its original meaning and became
a synonym of general devastation, too. The actual analysis does not intend to treat
the events of the military campaign, but rather the road to the disaster as well as the
economic and social consequences of the shocking event: i.e. the circumstances of
the evolution and the overcoming of the crisis. As the Mongol invasion of 1240–
1242 had an effect on a number of the countries in Central and Eastern Europe, both
the reason for the crisis and the overcoming of the catastrophe differed considerably.